Conceptual Design Support Tool For Subsea Equipment Processing System - Sabri, Shafiq Hakimi (UNIVERSITI TEKNOLOGI PETRONAS, 2012)
Conceptual design is a critical process where initial design of equipment drawing which exhibiting ideas to the stage of creating a number of alternate solutions for the designated problem. This process generates Design Concepts and the supporting analysis in order to help determines the feasibility of each of the alternative solutions. This thesis will focus on the Conceptual Design Support Tool for Subsea Processing Equipment, or known as CDST. This design tool is created with the purpose of assisting the designers. This tool is the only design tool known for supporting the oil and gas domain. In this project, the author is emphasizing on enhancing the current capability of the design tool by adding new design concepts into the design tool database. The methodology of project involves preliminary research work regarding the domains related to this project, familiarization of the support tool, a deeper study in subsea processing equipment, researching and identifying new design concepts and validating the concepts, embedding the validated concepts into the concept library, and the capability demonstration of the new enhanced design support tool. A comparison between morphology chart generated by CDSTsped and CDST are conducted in which focusing on Two-phase Separator and Three-phase Separator. A total of 24 new design concepts are embedded into the concept library. The concept variants are for both phase of separator increased dramatically from 36 to 2100 of concept variants for Two-phase Separator and from 108 to 18900 of concept variants for Three-phase Separator.